Conversion of minor children to Islam in Malaysia : Whither consent of parents? - Abdul Rahman, Narizan (2008)
Issues relating to conversion to Islam in Malaysia have drawn the interest of many segments of Malaysian public and been given wide coverage recently, in particular pertaining to the conversion of minor children. The issue at stake here is, does it or does it not requires consent of parents prior to the conversion? If the answer is positive, further explanation follows whether the law requires consent of both parents prior to the conversion or one parent's approval is sufficient to constitute a consent. Therefore, this paper seeks to discuss the issue in its perspective and hence relevant resolution may be offered. To date, certain decisions of Malaysian courts have shown conflicting trends whereby some decisions affirmed the requirement of consent of both parents while in some other cases, the consent of one parent only is sufficient for minor children to convert to Islam. The case of Chang Ah Mee is often cited to support the proposition of requirement of consent of both parents prior to the conversion of minor children to Islam. Nevertheless, new interpretations have been adopted by courts in post Chang Ah Mee era. With this framework as a background, this paper seeks to analyze the current situation within civil and Islamic law perspectives.